Interleukin 8 Molecular Interplay in Allergic Rhinitis and Chronic Rhinosinusitis with Nasal Polyps: A Scoping Review - Romica Cergan; Ovidiu Berghi; Mihai Dumitru; Daniela Vrinceanu; Felicia Manole; Gabriela Cornelia Musat; Alina Lavinia Antoaneta Oancea; Crenguta Serboiu (Life)
The present scoping review underlines the molecular interplay between allergic rhinitis (AR), chronic rhinosinusitis with nasal polyps (CRSwNP), and interleukin-8 (IL-8). A query of PubMed database resulted in the inclusion of 34 articles in the final analysis of this scoping review. IL-8 is one interconnecting immune mediator in the physiopathology of AR and CRS. An influx of cytokines, such as interleukin (IL)-4 and IL-13, occurs from mast cells, four to six hours after the initial response signifying the development of the late-phase response allowing the entrance of eosinophils, basophils, and T-lymphocytes at the level of nasal mucosa. Chronic rhinosinusitis (CRS) is a chronic inflammatory disease that occurs in the mucosa of the nasal cavity and sinuses with two external phenotypes, but with molecular mechanisms that overlap with allergic rhinitis. Interleukin 8 induces neutrophil chemokinetic movement providing a chemotactic or directional cue. Clinical and fundamental studies established an implication of IL-8 in the disease mechanism of allergic rhinitis and CRSwNP. Moreover, there is still missing a randomized, large-cohort study with three patients groups (normal control, AR, CRSwNP) that analyzes the impact of IL-8 simultaneously. Future possible developments could focus on IL-8 as possible target for biologic treatments.